PENGALAMAN IBU YANG MENGALAMI BABY BLUES : LITERATURE REVIEW - Pazriani, Annisa Pir Laily (Tanjungpura Journal of Nursing Practice and Education, 2021)
Background: For most women, pregnancy, and birth could be simply daily events or even the greatest gift they have been waiting for, while for a small number of them, pregnancy and birth could become a life conflict while they are becoming mothers. This eventually may affect their mental health. The mental health problem might be related to an affective disorder where the most common type is baby blues. Baby blues in new mothers is expressed as unhappiness and being overly sensitive. These unintentional behaviors may cause mothers to neglect their babies which if left unmanaged it may harm the babies. The experience of baby blues faced by mothers is different, therefore researchers want to see a variety of experiences of mothers with baby blues.  Aim: To identify the experience of mothers with baby blues.  Method: This literature review was conducted by searching for articles from the database of Google Scholar, Researchgate, Sciencedirect, and Sage Publishing. Keywords : experience of postpartum blues, a qualitative study of postpartum blues. The SPIDER method was used for the analysis.  Result: The literature review yielded seven related articles that meet the criteria. From the articles, we found the experience of baby blues includes factors causing baby blues, mothers"™ feelings experiencing baby blues, and mothers"™ measures to overcome baby blues.  Conclusion: In this literature review, we include discussions about mothers"™ experiences that can be used as an informative source for mothers, nurses, and midwives who treat baby blues, as well as for the general population so that they know and be more aware of this issue.  Keywords: experience, baby blues, mother